A comparative study on spatial configuration of human settlements in Riparian Area (Case studies : Old Kampoong and Colonial Settlements in Palembang - Adiyanto, Johannes; Romdhoni, M. Fajri; Warlika, Hendi (Institut Teknologi Sepuluh Nopember, 2017)
Palembang is the city which is divided by Musi River. Palembang is also one of the oldest city in Indonesia. Many old settlements were built in riparian area. This geographic condition of Palembang becomes background of this research. The research questions are: what is the discrepancy between Kampoong and Colonial Settlements in spatial configuration? Does the Musi River have influence in spatial configuration on that case? This research using the space syntax analysis with the following three steps of analysis: convex map analysis, axial map analysis and visibility graph analysis. For case studies, this research names two different settlements: old Kampoong (3-4 Ulu and 10 Ulu) and Colonial settlements (Komperta Plaju and Komperta Bagus Kuning) and we use Kampung Kapitan (7 Ulu) for the comparation. As the result of this research shows that between Kampoong and Colonial Settlements have some discrepancies in spatial configuration. In Kampoong, they have a small ‘void space’, many streets between houses and the organic patterns. In Colonial settlements, the spatial configuration is planned well with grid pattern. In context influences of Musi River to the settlements, only Bagus Kuning complex that has a closed relationship with rivers because those settlements have a connection between inner ‘void space’ with riparian ‘void space’.